Effect of Power-Assisted Functional Electrical Stimulation (PAFES) and Occupational Exercise on Motor Unit Activity of Extensor Digitorum Communis and Hand Dexterity in Post-stroke Patient - Yusuf Roni; Sri Mardjiati Mei Wulan; I Putu Alit Pawana (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Weakness of upper extremity can affect the ability to perform daily activities in post-stroke patients. Power-Assisted Functional Electrical Stimulation (PAFES) may give motor reeducation and sensory feedback to improve motor recovery through neuroplasticity.Aim: To evaluate the effect of PAFES and occupational exercise on post-stroke patient hand dexterity and motor unit activity of extensor digitorum communis muscle.Material and methods: Twenty post-stroke patients enrolled in the study were divided intervention group whom received PAFES and occupational exercise, and control group whom received occupational exercise only. Each group underwent 30 minutes per session of treatment, 5 times a week, for 3 weeks. The Root Mean Square (RMS) for measuring motor unit activity of extensor digitorum communis muscle; Box and Block Test (BBT) and Nine Hole Peg Test (NHPT) for measuring hand dexterity were evaluated before and after intervention.Result: There were significant improvements of RMS (p<0.001), BBT (p<0.001) and NHPT (p=0.002) in intervention group after receiving PAFES and occupational exercise. The improvement of BBT in intervention group was significant compared with control group (p=0.028), however, no significant improvement of NHPT was found between groups.Conclusion: PAFES and occupational exercise could improve motor unit activity of the extensor digitorum communis muscle and hand dexterity in post-stroke patient.